Analysis of the Calorific Value and Specific Gravity of Breadfruit Peel Bioalcohol (Artocarpus Altilis) as an Alternative Fuel at Various Distillation Temperatures - Hendry Sakke Tira; Mirmanto; Iwanuddin; Salman; Sudirman (Jurnal Penelitian Pendidikan IPA, 2023)
The objective of this study was to investigate how distillation temperature affected the specific gravity (SG) and calorific value of bioalcohol derived from breadfruit peels (Artocarpus altilis) as an alternative fuel. The process of producing bioethanol from breadfruit peels begins with pretreatment of the peels, followed by hydrolysis with hydrochloric acid, fermentation, and finally distillation. The hydrolysis process used 20% hydrochloric acid in a volume of 25 ml, and the fermentation took 6 days with a mass of 30 gr of yeast Saccharomyces cerevisiae. The distillation process lasted two hours, with temperatures varying between 70, 80, and 90°C. This study yielded the highest alcohol content of 72.80% at 70°C and the highest volume of bioalcohol of 35.67 ml at 90°C. Meanwhile, the best Specific Gravity (SG) at 70°C was 0.8393. Furthermore, the calorific value test results revealed that the calorific value increased with increasing alcohol content. The highest calorific value obtained was 23003.406 J/gr, which was close to the ethanol calorific value of 29700 J/gr, while the lowest calorific value obtained was 22339.008 J/gr at a distillation temperature of 90°C